Manajemen Informasi Administrasi dan Kearsipan Menggunakan Aplikasi SRIKANDI dalam Pelayanan Publik di Setjen DPR RI - Elisabeth Sonia Asa; Yoakim Rembu (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
The Srikandi application is an electronic-based management information system designed to support digital transformation in administration and archiving to enhance efficiency, transparency, and accountability in public services, particularly within the Secretariat General of the Indonesian House of Representatives (Setjen DPR RI). This study aims to analyze the implementation of the Srikandi application, evaluate its impact on work efficiency and service quality, and identify the main challenges in its adoption. This research employs a qualitative approach with a descriptive method. The findings indicate that the Srikandi application has successfully improved administrative efficiency through features such as electronic signatures and real-time document tracking, as well as supporting the restructuring of organizational work processes. However, several key challenges remain, including slow system performance, low user competence, resistance to new technology, limited accessibility for the public, and data security risks. The implications of this study highlight the importance of enhancing user competence through training, optimizing technological infrastructure, and strengthening data security policies. This study is expected to serve as a reference for other government institutions in adopting digital technologies to support more responsive and accountable public services.